The Effect of Principal’s Leadership and Infrastructure Support on Teacher’s Performance - Ulfah, Rezka; Harapan, Edi; Mulyadi, Mulyadi (Journal of Social Work and Science Education, 2023)
Leadership is a birth from a protracted process of change in a person rather than a position or title. Teacher performance is always the center of attention because it is one of the factors in improving student achievement, so that teacher performance is always considered and various efforts are made to improve teacher performance. The infrastructure resources that Gunung Raja District schools have to support the educational process are insufficient to assist teachers in their instruction and prevent the development of students’ knowledge and abilities. The researcher is motivated to study "The Influence of Principal Leadership and Infrastructure Support on the Performance of Public Elementary School Teachers in Tanjung Raja District" in light of these circumstances. The survey research approach was employed in this study. 262 instructors, including the principals of 26 public primary schools in the Tanjung Raja District, made up the study’s population. Out of a total population of 262 respondents in 26 public elementary schools in Tanjung Raja District, the researchers selected 144 participants In this research, the technique and data collection that researchers use is through questionnaires, observation, and documentation. The conclusions: The effectiveness of the teachers is significantly influenced by the head of the school’s leadership. The performance of the teachers improves in direct proportion to the amount of leadership exercised by school administrators. The infrastructure has a considerable impact on the caliber of instructor performance. The quality of the school’s infrastructure and its infrastructure infrastructure will affect the teacher’s performance. Infrastructure has significantly and significantly impacted the principle of the school’s leadership.